Development of a Cartesian Painter Robot for Construction Industry - Iqbal, A. K. M. Parvez (2002)
Nowadays robots are widely used in many applications such as in factories, the mining industries, the automobile industry etc. Currently, the application of robot is still not widely implemented in construction industry. In construction industry, robots are designed to increase speed and improve the accuracy of construction field operations. It can also be used to do hazardous and dangerous job in construction. For example, house painting is done manually. This process can be simplified using a special dedicated robot. It is very difficult and troublesome for human to work in an upright position especially for painting, cleaning and screwing in the ceiling for a long time. Painting in an upright position is also very dangerous for the eyes. To overcome this difficulty, a painter robot system is proposed and developed. The main objective of this project is to develop a three-degree of freedom (DOF) painter robot and its intelligent system. In order to achieve the main objective, the following works are carried out: Development of the mechanical structure of the robot. This includes the positioning module and end-effector module. The positioning module is divided into three parts namely, X-axis module, Y-axis module and Z- axis module. Development of the electrical and electronic system of the robot. These include its power distribution system, sensor system, motor driver system, electro-pneumatic system and programmable logic controller and development of the controlling program of the robot. The proposed painter robot has three degree of freedom (DOF). For X direction, a single-phase induction motor and a chain-sprocket mechanism are used. Two limit switches and two electronic sensors are used to limit the movement i n X direction. Another sensor is used to position the robotic arm along the X direction. For Y direction, two limit switches are used to limit the movement in Y direction. Two sensors are used to protect the robotic arm along the Y direction. The single-phase motor with an inverter is utilized to control the speed of the robot in Y direction. For Z direction, a parallelogram structure and a ball-screw mechanism are used in this project. A single-phase brake motor and a photoelectric sensor are used to control the position in Z direction . Two limit switches are used to limit the movement in Z direction. The proposed robot is used to paint the ceiling of the houses. The paint i s sprayed by the robot automatically using the pneumatic system. The software part involves the design and development of the system control software. The system control software i s created using FP WIN OR PLC programming software. This project implements the Matsushita NAIS FPO programmable logic controller (PLC) to control the overall system of the machine. From the tests conducted on the painter robot operating according to its original plan.